3.15 – Nonmetallics - Construction Minerals - Robert M. Dreyer (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1976)
AGGREGATE With an annual domestic production of over 1.6 billion tons at a value of over $2 billion (see Table 15.1.1), the production of aggregate (crushed rock, sand, and gravel) is a basic industry of utmost economic importance. Because of the role of aggregate materials as essential ingredients of concrete, asphalt surfacing, and plaster, their delivered prices are major factors in determining the cost of construction. The annual domestic production comes from nearly 10,000 plants. About 15% of these plants account for over one-half the production. In a rapidly inflating economy, the average mine sales price of aggregate has remained relatively stable. The actual mine sales prices, however, vary greatly depending on quarrying costs in various parts of the country. Of much more importance in construction costs, however, is the delivered price of aggregate. This varies for each job, depending on the distance from the quarry and resulting transportation costs, as well as the initial cost at the mine. Because of a proliferation of regulations limiting new quarries in the vicinity of the encroaching urban sprawl, the average distance which aggregate must be transported has been increasing rapidly. Although it is impossible to derive an average delivered cost for aggregate, it should be noted that even an increase of only $1 per ton in average delivered cost over the last decade (probably a minimal assumption) would mean an annual cost $1.5 billion higher than ten years ago. In recent years, structural engineering considerations, as well as an increasing use of lightweight concrete blocks, have resulted in a rapidly increasing demand for lightweight concrete and plaster, the essential ingredient of which is lightweight aggregate. Principal lightweight aggregates are: pumice, slag, perlite (thermally expanded hydrous volcanic glass), vermiculite, and expanded shale, formed by the thermal expansion of shale and slate. The United States now has the capacity to expand, annually, over 13 million tons of shale and slate and to expand over 600,000 tons of perlite. In locating a site for aggregate production. the following factors must be considered: (1) tonnage available; (2) quality of aggregate (including local variations); (3) distance from major use areas; (4) transportation costs, including those resulting from present and possible future haulage restrictions; (5) zoning regulations; (6) operating costs, including the cost effects of compliance with local regulations governing blasting, air pollution, water pollution and drainage, noise levels, and operating periods. At one time, locating a suitable site for the production of crushed rock, sand, or gravel, in most areas, was regarded as an extremely simple task. In the past few years, however, finding a site for profitable production of aggregate has assumed ever-increasing com-